2013
DOI: 10.1111/joie.12024
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Patenting and Software Innovation

Abstract: Strategic patenting is widely believed to raise the costs of innovating, especially in industries characterised by cumulative innovation. This paper studies the effects of strategic patenting on R&D, patenting and market value in the computer software industry. We focus on two key aspects: patent portfolio size, which affects bargaining power in patent disputes, and the fragmentation of patent rights (‘patent thickets’) which increases the transaction costs of enforcement. We develop a model that incorporates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(94 citation statements)
references
References 52 publications
(100 reference statements)
5
85
2
2
Order By: Relevance
“…However, other studies found more intricate relationships: e.g., Hashmi and Biesebroeck (2006) find an inverted-U relationship between innovation and market share, and Noel and Schankerman (2013) find a dynamic intertemporal relationship between sales and innovation. Hu (2010) finds that patents increased not due to the expansion of firms' own sales, but by increase in competing imports.…”
Section: Empirical Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, other studies found more intricate relationships: e.g., Hashmi and Biesebroeck (2006) find an inverted-U relationship between innovation and market share, and Noel and Schankerman (2013) find a dynamic intertemporal relationship between sales and innovation. Hu (2010) finds that patents increased not due to the expansion of firms' own sales, but by increase in competing imports.…”
Section: Empirical Findingsmentioning
confidence: 98%
“…An additional point we note is that in our panel, the correlation between firms' market share and HHI is 0.02 -so there is no obvious collinearity issue. 16 E.g., Acs and Audretsch (1988), Blundell et al (1995Blundell et al ( , 1999, Aghion et al (2005), Hashmi and Biesebroeck (2006), Hu (2010), Hashmi (2013), and Noel and Schankerman (2013).…”
Section: Own Market Share Hhi and Patentsmentioning
confidence: 99%
“…Patents have also become tradable assets that play a crucial role for firm value in many technological fields. Additionally, advancements in the market for technology allow patent holders active in complex technologies to generate licensing revenues (Gulati, 1998;Eisenhardt and Schoonhoven, 1996;Arundel and Patel, 2003;Noel and Schankerman, 2006).…”
Section: Collaboration and Strategic Motives To Patentmentioning
confidence: 99%
“…Competitive market conditions also induce patenting for strategic reasons (Cohen, Nelson and Walsh 2000;Hall and Ziedonis, 2001). Thus in highly competitive industries such as semiconductor, software and electronics, many firms have built large patent portfolios in order to reduce their vulnerability to infringement litigation by their rivals (Ziedonis, 2004;Noel and Schankerman, 2006;Cockburn and MacGarvie, 2009). In these industries, which are characterized by complex technologies with hundreds of patentable elements embodied in one product, no single firm is likely to hold all the rights necessary for a product's commercialization.…”
Section: Hypothesesmentioning
confidence: 99%
“…While the size of the market signifies the potential for exploiting a firm's knowledge resources, the need for protecting those resources derives from the extent to which local manufacturers are able to imitate a firm's technologies (Chan, 2010;Hu, 2010), and the degree of competition in the local market (Hall and Ziedonis, 2001;Ziedonis, 2004;Noel and Schankerman, 2006;Cockburn and MacGarvie, 2009;Hu 2010). To capture the imitative capability of local manufacturers, we introduce a novel measure, defined as the number of triadic patents of which one or more inventors are located in the host country.…”
Section: Introductionmentioning
confidence: 99%